Commentaries on European contract laws - Jansen, Nils; Zimmermann, Reinhard, 1952- (Oxford, United Kingdom ; New York, NY : Oxford University Press, 2018)
Written by a series of experts in European contract law, this work manifests itself as a set of comprehensive historical and comparative commentaries, providing the basis for understanding and evaluating international texts, and for assessing to what extent they restate European law in a credible and appropriate manner.
Includes bibliographical references and index.
Keywords: Contracts -- Europe; Contracts; Europe